Geodynamic processes in the area Quillcay river, Huaraz-Ancash - Chacón, Néstor (2005)
The climatologically changes that involve the global heating, have produced in the last decades a great reduction of glacial areas on earth, and this is evidenced by the glacial back stripping The area of study is situated into a seismotectonic zone where an intercordilleran segment has a Cordillera Blanca’s glaciers, that produces a lot of ice2 s falls, moraines landslides and great rocks. These materials fall in to glacial lakes and produce a violent damage. Huaraz city is in the Quilcay2 s alluvial fan, and consists of the fluvial-alluvial sediments Historically in Huaraz have been reported events like landslides that evidence the risk factor and increase the vulnerability of the zone due to deglatiation and lacustrine phenomena’s of Palcarraju mountain and Palcacocha lake. For the mitigation of the risk we are showing some instructions that must be diffused to the most of the people.